Factors associated with serum thyroglobulin levels in a population living in Belarus. (27th April 2013) - Cahoon, Elizabeth K.; Rozhko, Alexander; Hatch, Maureen; Polyanskaya, Olga; Ostroumova, Evgenia; Tang, Min; Nadirov, Eldar; Yauseyenka, Vasilina; Savasteeva, Irina; McConnell, Robert J.; Pfeiffer, Ruth M.; Brenner, Alina V.
Summary Objective Serum thyroglobulin (Tg) has been associated with a number of thyroid disorders and has been proposed as an indicator of iodine deficiency in a population. However, few studies have addressed the epidemiology of Tg in a population‐based setting or in the context of exposure to radioactive iodine‐131 (I‐131). Our objective was to evaluate baseline levels of Tg in relation to sociodemographic characteristics, iodine status and thyroid function for individuals exposed to I‐131. Design A population‐based cohort assembled in Belarus following the Chornobyl accident provided demographic factors, clinical data and physiological measurements. Participants Our analytical sample included 10 344 subjects of whom 7890 had no thyroid disease and 2454 had evidence of structural or functional thyroid abnormality. Measurements Standardized assays were used to measure serum Tg, urinary iodine, TSH and antibodies to Tg and thyroid peroxidase. Ultrasound was used to assess the presence of nodules and estimate thyroid volume. Results In the fully adjusted model, percent change in Tg was significantly increased among females, smokers and subjects of older age and Tg increased with decreasing urinary iodine concentration, increasing serum TSH and increasing thyroid volume (P‐values for trend <0·0001), and presence of thyroid nodules (P < 0·05). We found a complex interaction between region of residence, rural/urban living, presence/absence of thyroid abnormalities and serum Tg (P < 0·0001). Conclusions In residents of Belarus, serum Tg is significantly related to presence of thyroid abnormalities as well as indicators of thyroid function and iodine deficiency and, therefore, could be used to characterize the iodine status and thyroid function of individuals in the context of epidemiological study.